ELEMENTS TOWARDS A CREATIVE HERMENEUTICS: METHODOLOGICAL PRECAUTIONS IN THE STUDY OF RELIGION - Axinciuc, Madeea (European Scientific Journal, ESJ, 2013)
The study aims at a revision and a re-appraisal of Eliade’s allusive theory regarding the prerequisites and the necessity of reconfiguring the study of religion as a new integrative reasearch area relevant for the understanding of human mind. Special emphasis will be laid on highlighting, in a critical manner, the methodological framework envisaged by Eliade for the development of this new ‘Phenomenology of the Mind’, with a special focus on his approach indicating towards a ‘creative hermeneutics’. Terms and concepts such as ‘perspectivism’, ‘creativity’, ‘scientific discourse’ are revisited in the light of the new methodological framework under discussion.